Both heterozygous and homozygous alpha+ thalassemias protect against severe and fatal Plasmodium falciparum malaria on the coast of Kenya. - Williams, T; Wambua, S; Uyoga, S; Macharia, A; Mwacharo, J; Newton, C; Maitland, K (2005)
Although the alpha+ thalassemias almost certainly confer protection against death from malaria, this has not been formally documented. We have conducted a study involving 655 case patients with rigorously defined severe malaria and 648 controls, frequency matched on area of residence and ethnic group. The prevalence of both heterozygous and homozygous alpha+ thalassemia was reduced in both case patients with severe malaria (adjusted odds ratios [ORs], 0.73 and 0.57; 95% confidence intervals [95% CIs], 0.57-0.94 and 0.40-0.81; P = .013 and P = .002, respectively, compared with controls) and among the subgroup of children who died after admission with severe malaria (OR, 0.60 and 0.37; 95% CI, 0.37-1.00 and 0.16-0.87; P = .05 and P = .02, respectively, compared with surviving case patients). The lowest ORs were seen for the forms of malaria associated with the highest mortality-coma and severe anemia complicated by deep, acidotic breathing. Our study supports the conclusion that both heterozygotes and homozygotes enjoy a selective advantage against death from Plasmodium falciparum malaria.